(untitled) (Revista de História Regional, 2025)
In the Rio Doce valley, particularly in the Urupuca valley, in the municipality of Itambacuri, between 1945 and 1961, agrarian conflicts intensified, as demonstrated by the sources used: land legitimization processes, newspapers and interviews. This constitutes a particular case of agrarian conflicts in the agricultural frontier areas, due to the presence of communities of small-scale farmers, cattle ranchers and large capitalist steel enterprises. These conflicts are inseparable from the historical formation of the Rio Doce territory, particularly in the northern portion, between the cities of Governador Valadares and Teófilo Otoni. The study demonstrates that the concepts of “expansion front” and “pioneer front” are operational for understanding the rural world and agrarian conflicts in the frontier areas.